2020
DOI: 10.1021/acs.oprd.9b00471
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Optimization, and Large-Scale Preparation of the Low-Dose Central Nervous System-Penetrant BACE1 Inhibitor LY3202626 via a [3 + 2] Nitrone Cycloaddition

Abstract: Herein we report a summary of the synthetic development of LY3202626 from the initial discovery route to a final route that was scaled to make 150 kg. Key developments include the use of a [3 + 2] cyclization to set the cis ring junction of the formed isoxazoline, a one-pot thiazine formation, and three different ways to install the aniline: (1) Cu-catalyzed azide coupling and reduction, (2) nitration and reduction, and (3) Buchwald coupling with acetamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Compounds 20−22 were prepared in one step from diamine 19 and the corresponding acid chloride as described in Scheme 3. 28 Amides 20−22 displayed potency at least 25-fold greater than that of LY2886721 with high LEAN values, indicating that the addition of heavy atoms efficiently translated to higher BACE1 potency (Table 4). The X-ray structure of compound 22 (Figure 5) showed that the methoxypyrazine group filled the S3 pocket of the BACE enzyme.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Compounds 20−22 were prepared in one step from diamine 19 and the corresponding acid chloride as described in Scheme 3. 28 Amides 20−22 displayed potency at least 25-fold greater than that of LY2886721 with high LEAN values, indicating that the addition of heavy atoms efficiently translated to higher BACE1 potency (Table 4). The X-ray structure of compound 22 (Figure 5) showed that the methoxypyrazine group filled the S3 pocket of the BACE enzyme.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Nevertheless, we elected to explore compounds 20 – 22 and make data-driven decisions regarding their strengths and weaknesses. Compounds 20 – 22 were prepared in one step from diamine 19 and the corresponding acid chloride as described in Scheme …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting first-generation route outlined in Scheme consists of 19 synthetic stages and proceeds in 4.8% overall yield. Process highlights of the route include multiple crystalline intermediates in the late stages, a diastereoselective [3 + 2] cycloaddition (dr 13:1) to establish the relative stereochemistry of all three stereogenic centers (Stage 5), and a classical diastereomeric salt resolution utilizing dibenzoyl- d -tartaric acid ( d -DBTA) to isolate the desired enantiomer whose configuration was confirmed by X-ray (Stage 7). Pyrazinoic acid 16 was prepared from acid 18 in 4 steps employing deoxofluorination as the key step.…”
Section: Resultsmentioning
confidence: 99%